Down-regulation of Runx1 Expression by TCR Signal Involves an Autoregulatory Mechanism and Contributes to IL-2 Production - Wong, W.F.; Kurokawa, M.; Satake, M.; Kohu, K. (American Society for Biochemistry and Molecular Biology, 2011)
Runx1 transcription factor plays multiple roles in T cell development, differentiation, and function. However, the regulatory mechanisms and functional significance of high Runx1 protein expression in resting peripheral CD4+ T cells is not well understood. Here, we demonstrate that T-cell receptor (TCR) activation down-regulates distal Runx1 transcription, resulting in a significant reduction of Runx1 protein. Interestingly, this down-regulation of distal Runx1 transcription appears to be mediated through a negative auto-regulatory mechanism, whereby Runx1 protein binds to a Runx consensus site in the distal promoter. Through the use of Runx1-overexpressing cells from transgenic mice, we demonstrate that interference with TCR-mediated Runx1 down-regulation inhibits IL-2 production and proliferation in activated CD4+ T cells. In contrast, using Runx1-deficient cells prepared from targeted mice, we show that the absence of Runx1 in unstimulated CD4+ T cells results in IL-2 derepression. In summary, we propose that high levels of Runx1 in resting CD4+ T cells functions negatively in the regulation of IL-2 transcription, and that TCR activation-mediated down-regulation of Runx1 involves negative auto-regulation of the distal Runx1 promoter and contributes to IL-2 production.